Pengaruh Pelatihan Caring terhadap Perilaku Memberikan Asuhan Keperawatan pada Mahasiswa Saat Rotasi Klinik di Politeknik Depkes Palangka Raya - Maria Magdalena Purba; Ova Emilia; Gandes Retno Rahayu (Asosiasi Institusi Pendidikan Kedokteran Indonesia, 2013)
Background: Caring in nursing is a very basic component, as the heart of profession, Which means that caring is a fundamental component, and central and unique focus of nursing. Caring, which is a core of nursing practice, must grow from self and deepest heart to help other people since being a nursing student so that caring in nursing education, must be placed as main competency in nursing education. The aim of this research to evaluation the efficacy of caring training in improving understand cognitive, affective and psychomotor competencies of caring, among students during clinical periodMethod: This research used quasi experiment non-randomized control group pretest-posttest design. Respondents of research were nursing students of Poltekes Palangka Raya, Semester V, regular class, X-A period, with total of 37 respondents as intervention group and regular class of X-B period with total of 35 respondents as control group.Results: Data were analyzed using descriptive and inferential statistical analyses. Results of research indicated that cognitive, affective and psychomotor competencies of caring in nursing students with caring training did not show significant effect (cognitive: p-value = 0,21, affective: p-value = 0.58, psychomotor: p-value = 0.07); however, the average scores were higher among student received caring training The caring behavior showed no difference between male and female students.Conclusion: There is insignificant difference between students with caring training and students without caring training. The training should be modified as suggested in the paper.